2014
DOI: 10.1007/s00737-014-0463-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between postnatal maternal depression and psychological outcomes in adolescent offspring: a systematic review

Abstract: Postnatal depression (PND) affects approximately 10-20 % of new mothers in developed countries, with accumulating research documenting its adverse impact on not only the mother but also the wider family. Longitudinal studies assessing potential effects of maternal PND on offspring are mounting, and it is therefore timely to investigate the long-term psychological outcomes for adolescent offspring who were exposed to PND in infancy. PsycINFO, Medline, and Embase databases were searched with key terms for Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 59 publications
5
105
0
2
Order By: Relevance
“…al., 2015). A combination of antenatal and postnatal maternal 4 depression demonstrates long-term effects on the cognitive development and depressive illness risk of children (Asselmann, Wittchen, Lieb, & Beesdo-Baum, 2015;Sanger, Andrew, & Ramchandani, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., 2015). A combination of antenatal and postnatal maternal 4 depression demonstrates long-term effects on the cognitive development and depressive illness risk of children (Asselmann, Wittchen, Lieb, & Beesdo-Baum, 2015;Sanger, Andrew, & Ramchandani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…al., 2015). A combination of antenatal and postnatal maternal 4 depression demonstrates long-term effects on the cognitive development and depressive illness risk of children (Asselmann, Wittchen, Lieb, & Beesdo-Baum, 2015;Sanger, Andrew, & Ramchandani, 2015).One of the mechanism of transmission of risk for mental health disorders is thought to be associated with the mother's attachment security and her behaviour with the child, and there is growing evidence to suggest maternal attachment style can be seen as a mediator (Toth, Cicchetti, Rogosch, & Sturge-Apple, 2009). However, women with a pre-existing negative model of the self and others have been shown to be at higher risk of developing PND (Wilkinson & Mulcahy, 2010).…”
mentioning
confidence: 99%
“…Research has focused mainly on the exposure to maternal depression as influencing child effects. A recent review of 16 studies investigating maternal postnatal depression and offspring consequences, reported that mothers' postnatal depression was associated with offspring negative cognitive outcomes, but suggested evidence of other effects were limited and conflicting (Sanger et al, 2015). Other studies point to a possible bidirectional pathway between mother and child psychopathology and a few studies have examined a reverse causal pathway.…”
Section: Child and Adolescent Behaviour Problemsmentioning
confidence: 99%
“…Evidence shows exposure to maternal poor mental health has the capacity to influence offspring development , Sanger et al, 2015, Parsons et al, 2012. Much of this evidence points to the effects of peripartum maternal depression on early child development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation